Effects of the range of light wavelengths on the phototactic behaviour and biological traits in the melon thrips, Thrips palmi Karny (Thysanoptera Thripidae). Issue 2 (4th March 2018) - Murata, Mika; Hariyama, Takahiko; Yamahama, Yumi; Toyama, Mina; Ohta, Izumi
Abstract : Phototactic behaviours and the toxic effects of certain light wavelengths have been used to control insect pests. However, in many species, little is known about this innate behaviour and the effects on physiological and biological traits related to the emission and/or reflection spectra of light. The present study investigated the phototactic behaviour and the effects on physiological and biological traits of a small insect, the melon thrips, Thrips palmi (Thysanoptera Thripidae). Using seven different light-emitting diode panels (355, 405, 470, 525, 590, 660 and 735 nm) under dark conditions, it was found that this species was attracted to a wide range of light from short to long wavelengths in all tested lights. Comparing the light intensities required to gather 50% of individuals to the panels revealed that the short wavelength region (λmax 470 nm) was more effective than longer wavelengths. None of the seven wavelengths examined affected biological traits such as adult emergence and oviposition in the melon thrips. Comparison with previous studies indicates that these results are species specific and provide data that will be helpful in developing future pest-control measures using lights.